PENGUJIAN SIFAT MEKANIS BATAKO PEJAL MENGGUNAKAN GABUS KELAPA DENGAN VARIASI VOLUME GABUS 10%, 15%, 20% DAN 50% - ., Arfan; ., Herwani; Supriyadi, Asep (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2015)
Concrete brick is one infill material made from a mixture of cement, sand, with or without added ingredients and a little water. The amount of waste oil cork unprocessed as possible in the area of Pontianak in West Kalimantan have spawned an idea to use it as an ingredient added in a mixture of solid brick, with the consideration that it will produce a lighter brick and relative quality equivalent to regular brick. So the research must be done to achieve that purpose. The composition of the mixture used in this study were 1 pc : 6 ps with the use of cork coconut variation of 10%, 15%, 20% and 50% of the volume of concrete brick. Stirring is done manually and printing using solid brick mold dimension of 10 cm x 20 cm x 40 cm. compressive strength test performed at the test specimen was 3, 7, 14 and 28 days. The test results showed that the use of cork coconut as an ingredient added in a mixture of brick causes decreased reach 2,127 MPa; 1,302 MPa; 0.901 MPa and 0.109 MPa. While heavy concrete bricks also decreased reached ,3 kg/m3; 1473,7 kg/m3; 1411,4 kg/m3 dan 832 kg/m3. Mean while, according to SK SNI 03-0349-1989 compressive strength of solid brick average of 2.5 MPa, under of 2.5 MPa, the brick does not meet the standards. Keywords: solid brick, Materials Cork Add coconut, and Compressive Strength.